Interactive effects of kindergarten organizational resources on classroom quality in an era of universalizing ECE in China. (2020) - Pan, Yue-Juan; Liu, Yan; Yang, Qing-Qing; Zheng, Xiao-Ling; Wu, Xin; Song, Li-Qin
Highlights: Fiscal funding has no significant link with teacher salary and child-teacher ratio. Fiscal funding has significantly positive association with instructional management. Instructional management mediates the link of fiscal funding with classroom quality. It is important to utilize resources to support teacher and instructional management. Abstract: The present study examined the interactive effects of organizational resources on classroom quality of 90 Chinese kindergartens using principal and teacher questionnaires and observational ratings of classroom practices. The results revealed that the average monthly teacher salary, child-teacher ratio and instructional management had significant direct associations with classroom quality, and the three-year average fiscal funding had a significantly positive association with instructional management and significant indirect association with classroom quality via the mediation of instructional management. The findings suggested that the allocation and organization of resources for teachers and instructional management in support of teachers and teaching are important for improving classroom quality, and that kindergarten leaders play a critical role in effectively transforming available resources into quality classroom practices.